Potential of ITO thin film for electrical probe memory applications. Issue 1 (31st December 2018) - Wang, Lei; Wen, Jing; Yang, Cihui; Xiong, Bangshu
ABSTRACT: Electrical probe memory has received considerable attention during the last decade due to its prospective potential for the future mass storage device. However, the electrical probe device with conventional diamond-like carbon capping and bottom layers encounters with large interfacial contact resistance and difficulty to match the experimentally measured properties, while its analog with titanium nitride capping and bottom layers also faces serious heat dissipation through either probe and silicon substrate. Therefore, the feasibility of using indium tin oxide (ITO) media for the capping and bottom layers of the electrical probe device is investigated by tailoring the thickness and electrothermal properties of the ITO capping and bottom layers within experimentally established range and subsequently calculating the resultant temperature at several predefined points based on a previously developed three-dimensional model. To meet the required temperature and to fit the experimentally reported values, the thickness, electrical conductivity, and thermal conductivity of the ITO capping and bottom layers are found to be 5 nm, 10 3  Ω −1  m −1, 0.84 W m −1  K −1, and 200 nm, 1.25 × 10 6  Ω −1  m −1, 0.84 W m −1  K −1, respectively. The practicality of using this optimized device to achieve ultrahigh density, ultralow energy consumption, ultrafast switching speed, low interfacial contact resistance, and high thermal reliability has also been demonstrated. Graphical Abstract: